ANALISIS PENERAPAN KEWAJIBAN NOTARIS DALAM MEMBERIKAN JASA HUKUM KENOTARIATAN SECARA CUMA-CUMA BAGI MASYARAKAT MISKIN - Arshandi, Aldi; Nuryanti, Aktris; Ismawartati, Ismawartati (Faculty Of Law, Universitas Tanjungpura, 2024)
AbstractThis article is entitled Analysis of the Application the Obligation of a Notary to Provide Legal Services in the Notary Field Free of charge for Poor Communities in Pontianak City. This research is an empirical legal research that is empirical juridical. This study uses primary data obtained from interviews and secondary data obtained from primary legal materials, secondary legal materials, and tertiary legal materials. The f ormulation of the problem in this study is 1) Does the Notary limit the Provisions of Article 37 of the Law Concerning the Office of a Notary in Pontianak City? 2) What are the Obstacles to a Notary in the Problem of the Provisions of Article 37 of the Law Concerning the Position of a Notary in Pontianak City? This research concludes that the implementation of providing legal services free of charge to the poor in Pontianak city has been going well, but it is only a service that connects with legalization, waarmerking and notary consultation, and the client's desire for a notarial deed only wants to reduce the costs of which is determined by UUJN. The research method used is the empirical juridical research method. The data collection technique used in this research is secondary data but does not rule out other possibilities for conducting field research by examining primary data. The results of this study are that notaries in the city of Pontianak have basically implemented the provisions of Article 37 of the Notary Office Law regarding the provision of legal services in the notary sector free of charge for people who can't afford it. However, in practice there are several characteristics of implementation that vary from one Notary to another. What hinders a Notary in carrying out the provisions of Article 37 of the Law on the Office of a Notary is caused, among other things, by ignorance of the public regarding reporting procedures and proving incapacity. AbstrakArtikel ini berjudul Analisis Penerapan Kewajiban Notaris Memberikan Jasa Hukum Kenotariatan Secara Cuma-Cuma Bagi Masyarakat Tidak Miskin Di Kota Pontianak. Penelitian ini merupakan penelitian hukum Empiris yang bersifat yuridis empiris. Penelitian ini menggunakan data primer yang didapat dari hasil wawancara dan data sekunder yang diperoleh dari bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Adapun rumusan masalah dalam penelitian ini adalah 1) Apakah Notaris Menjalankan Ketentuan Pasal 37 Undang-Undang Tentang Jabatan Notaris Di Kota Pontianak? 2) Apa Yang Menjadi Hambatan Notaris Dalam Melaksanakan Ketentuan Pasal 37 Undang-Undang Tentang Jabatan Notaris Di Kota Pontianak?. Penelitian ini menyimpulkan pelaksanaa pemberian jasa hukum secara cuma